Approximate analytical models for microsegregation considering the effect of dendrite arm coarsening - (:unkn) unknown (Trans Tech Publications Ltd, 2006)
In this study, simple analytical microsegregation models for constant cooling and parabolic growth are proposed considering dendrite arm coarsening effect with and without back diffusion. These simple models are compared with the Mortensen exact model and Voiler's models. It is shown that these analytical models can be used to predict approximately microsegregation in a binary alloy.
Keywords: Back diffusion; Dendrite arm coarsening; Dendritic solidification; Microsegregation; Modeling